Analysis of Islamic Character Education in Malay Culture in Early Childhood and Primary School - Aisyah Septarina; Indah Nur Aziza Alfatonah; Yonada Viossa Kisda; Maryamah Maryamah (Sustainable, 2023)
Character is a component of values in the standard view of behaviour in life. Any excellent character education programme should aim to develop good moral habits in students, not just instruct them on right and wrong. The problems of contemporary life can be met via character education founded on local wisdom principles. Society can instil values of independence, humanity, and devotion in students by imparting Islamic values through Malay culture. In this article, the author employs a descriptive qualitative research method with secondary data collection based on a case study approach. The study is focused on Islamic character education within Malay culture for early childhood and elementary school children. This is because Malay culture still firmly upholds Islamic religious values and customs, which can significantly influence the character development of children. Based on the research findings, it can be concluded that the implementation of Malay cultural character education for early childhood and elementary school children can be achieved through the following methods: 1) Organizing group games to instil character traits through Malay culture, 2) Implementing BMR (Riau Malay Culture) learning, 3) Education based on local wisdom, 4) Incorporating local wisdom values into character education within Riau Malay Culture, 5) Implementing Riau Malay Culture Local Content Learning (MULOK BMR).